The floating Island : the lost journals of Ven Polypheme - Haydon, Elizabeth (The Lost journals of Ven Polypheme, 2006)
When Charles Magnus Ven Polypheme begins his long-awaited journey, he gets lost at sea, is attacked by pirates and then held captive by those who think he can lead them to a mystical island and the Water of Life.